1996
DOI: 10.1177/0310057x9602400603
|View full text |Cite
|
Sign up to set email alerts
|

Association between Oxygen Delivery and Consumption in Patients Undergoing Cardiac Surgery. is There Supply Dependence?

Abstract: We studied the relationship between oxygen delivery (DO2) and consumption (VO2) in twenty patients undergoing cardiac surgery, in order to determine if VO2 was dependent on DO2 (pathological oxygen supply dependence). We measured VO2 from expired gas analysis (VO2G) and compared this to that calculated using the reverse Fick method (VO2F). Both VO2G and VO2F increased after cardiopulmonary bypass (P<0.001), without change in DO2 (i.e. oxygen extraction ratio increased). There was a significant relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Indeed, the much described oxygen debt theory after cardiac surgery has now become increasingly questioned. [9][10][11] In addition to the above, work by our unit (R.D. Slight and colleagues) has suggested that several patient and operative variables, normally associated with an increase in transfusion requirement, are not associated with an increase in RCV lost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the much described oxygen debt theory after cardiac surgery has now become increasingly questioned. [9][10][11] In addition to the above, work by our unit (R.D. Slight and colleagues) has suggested that several patient and operative variables, normally associated with an increase in transfusion requirement, are not associated with an increase in RCV lost.…”
Section: Discussionmentioning
confidence: 99%
“…Such results suggest that oxygen delivery remains adequate during times of acute stress despite a lowering of Hb concentration. Indeed, the much described oxygen debt theory after cardiac surgery has now become increasingly questioned 9‐11 …”
Section: Discussionmentioning
confidence: 99%
“…The possibility of such a RCV‐based system for transfusion is also supported by recent evidence that circulating RCV is relatively preserved in peri‐operative surgical patients (Orth et al ., 1998; Fransen et al ., 2001). Furthermore, the oxygen debt theory following cardiac surgery, which has long been used as an argument for a higher haemoglobin concentration, has now come under increasing scrutiny as to its likelihood (Hinds & Watson, 1995; Myles et al ., 1996; Ganushchak et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although no gold standard for measurement of has been established, the most frequently used methods have been the Fick‐derived method and indirect calorimetry [4, 7–9]. Calorimetry, which has been used extensively for research purposes in the critical care setting, is not widely available in clinical anaesthesia practice.…”
Section: Discussionmentioning
confidence: 99%
“…Calorimetry, which has been used extensively for research purposes in the critical care setting, is not widely available in clinical anaesthesia practice. The Fick‐derived method [3], based on the arteriovenous oxygen content difference, is an established technique and is a more generally available method for measurement of during anaesthesia [7, 8].…”
Section: Discussionmentioning
confidence: 99%